2007
DOI: 10.1021/jp075566p
|View full text |Cite
|
Sign up to set email alerts
|

General Methodology to Optimize Damping Functions to Account for Charge Penetration Effects in Electrostatic Calculations Using Multicentered Multipolar Expansions

Abstract: We developed a methodology to optimize exponential damping functions to account for charge penetration effects when computing molecular electrostatic properties using the multicentered multipolar expansion method (MME). This methodology is based in the optimization of a damping parameter set using a two-step fast local fitting procedure and the ab initio (Hartree-Fock/6-31G** and 6-31G**+) electrostatic potential calculated in a set of concentric grid of points as reference. The principal aspect of the methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…While the CP correction is short-ranged, it can be significant at equilibrium geometry of typical molecular complexes. Empirical damping formulas for treating CP have been proposed by several research groups. We have demonstrated that combining CP correction with point multipoles , leads to electrostatic interactions closely matching those from SAPT decomposition even at short distances while the added computational cost is minimal. This is a major step toward eliminating error cancellation between what are referred to as electrostatic and van der Waals interactions in classical FFs.…”
Section: Introductionmentioning
confidence: 99%
“…While the CP correction is short-ranged, it can be significant at equilibrium geometry of typical molecular complexes. Empirical damping formulas for treating CP have been proposed by several research groups. We have demonstrated that combining CP correction with point multipoles , leads to electrostatic interactions closely matching those from SAPT decomposition even at short distances while the added computational cost is minimal. This is a major step toward eliminating error cancellation between what are referred to as electrostatic and van der Waals interactions in classical FFs.…”
Section: Introductionmentioning
confidence: 99%
“…There have been previous attempts to incorporate the charge penetration effect into implicit solvent models, multipole-based electrostatic models, charge-density-based (including Gaussian multipole) models, , and combined quantum and molecular mechanics (QM/MM) models. , Generally, the charge penetration correction involves breaking the atom-centered point charge into an effective core and a valence electron density, as suggested by Gordon et al and Piquemal et al In this way, the electrostatic interaction between two atoms is described as a sum of interactions between core and valence charge densities, which can be modeled with empirical exponential functions. Alternatively, rigorous integration over the two charge densities can be used to model short-range electrostatic interactions, ,, with a significantly greater expenditure of computational effort.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we may say that the charge penetration effects are of both short and medium range. Including the charge penetration effect can significantly improve the description of the electrostatics in van der Waals interactions, and various procedures have been proposed to include this effect in molecular modeling. ,− For example, the charge penetration effects may be described by Gaussian-type functions or damping functions, and accurate electron densities, electrostatic potentials, and electrostatic interaction energies may be used for fitting parameters in these functions. The charge penetration effect has already been included in the development of some new force fields. ,, …”
Section: Introductionmentioning
confidence: 99%